Canadian Applied Mathematics QuarterlyJournalName 2000
DOI: 10.1216/camq/1032375140
|View full text |Cite
|
Sign up to set email alerts
|

Modeling equator-crossing currents on the ocean bottom

Abstract: ABSTRACT. Observations unambiguously show that deep ocean currents carry a significant amount of fluid across the equator. Away from the equator in either hemisphere, these currents are relatively quiescent so that planetary vorticity dominates relative vorticity within the fluid. Thus, the potential vorticity of cross-equatorial flow changes sign en route. The breakdown of geostrophic balance at the equator because of the vanishing horizontal component of the Coriolis force and the fact that potential vortici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…It is shown that the lack of fluid inertia in the FG model prevents the fluid from flowing against a dynamic pressure gradient, significantly restricting the motion. This is consistent with Choboter and Swaters [2000], who found that the FG model did not allow currents to flow as high on idealized topography as the shallow water model.…”
Section: Introductionsupporting
confidence: 90%
“…It is shown that the lack of fluid inertia in the FG model prevents the fluid from flowing against a dynamic pressure gradient, significantly restricting the motion. This is consistent with Choboter and Swaters [2000], who found that the FG model did not allow currents to flow as high on idealized topography as the shallow water model.…”
Section: Introductionsupporting
confidence: 90%
“…Notable differences between the shallow-water simulation and the FG simulation include the fact that the shallow-water lens penetrates the equator as it turns eastward where the FG eddy does not and that fluid in the shallow-water simulation flows to a higher point on the eastern slope than fluid in the FG simulation. These two differences hold over the whole range of parameters tested, and both are a result of the lack of fluid inertia in the FG model (Choboter and Swaters 2000).…”
Section: Emi Model Simulationsmentioning
confidence: 88%
“…This confirms that the EMI model derived is, indeed, a generalization of the Swaters and Flierl (1991) model to the case of varying Coriolis parameter, including allowing for f ϭ 0 in the domain. Choboter and Swaters (2000) investigated the dynamics of equator-crossing currents using simplified onelayer models and idealized topography. To explore the effects of baroclinicity on near-equatorial motions in the EMI model, we reproduce the simulations of Choboter and Swaters (2000), with and without a dynamically active upper layer, and quantitatively compare the results (Figs.…”
Section: Emi Model Simulationsmentioning
confidence: 99%
See 2 more Smart Citations